Late arrhythmia in adults with the Mustard procedure for transposition of great arteries: a surrogate marker for right ventricular dysfunction?. Issue 4 (1st October 2000) - Gatzoulis, M A; Walters, J; McLaughlin, P R; Merchant, N; Webb, G D; Liu, P
Abstract : OBJECTIVE: To examine the relation between ventricular dysfunction and late clinical arrhythmia in adults who underwent the Mustard procedure for transposition of the great arteries. DESIGN: Observational study based on periodic outpatient assessment of biventricular function. SETTING: Tertiary referral centre. INTERVENTIONS: Analysis of data from 12 lead ECGs, echocardiography, exercise radionuclide ventriculography, and magnetic resonance imaging. MAIN OUTCOME MEASURES: Clinical outcome and late onset clinical arrhythmia during follow up. ECG and ventricular function indices obtained before arrhythmia onset were used for analysis. RESULTS: 51 patients (mean (SD) age 25.7 (5.0) years) fulfilled entry criteria at a mean of 23.4 (4.0) years after the Mustard procedure. Late arrhythmia occurred in 11 (22%): sustained atrial flutter/fibrillation in 10, ventricular tachycardia in one. Compared with patients who remained arrhythmia free, patients with arrhythmia had longer QRS (129 (26) v 112 (16) ms, p = 0.01), greater QT dispersion (107 (28) v 51 (24) ms, p < 0.001), and increased ratio of right to left ventricular end diastolic diameter (2.4 (0.9) v 1.7 (0.7), p = 0.02), but no difference in wall thickness. Systemic ejection fraction was also reduced in the arrhythmia subgroup (at rest: 34.1 (13)% v 47 (16)%, p = 0.04; during exercise: 37.8 (12)% v 52 (17)%, p = 0.03). QRS duration correlated with right ventricular end diastolic diameter ( r  = 0.59, p < 0.001), suggesting a possible mechano-electric relation after the Mustard procedure. QT dispersion was the only predictor of clinical arrhythmia in multivariate analysis. CONCLUSIONS: Impaired ventricular function in adults with the Mustard procedure for transposition of the great arteries relates to clinical arrhythmia. Late atrial flutter/fibrillation may be a surrogate marker for ventricular dysfunction, and these patients may also be at risk of ventricular tachycardia.